Modeling and simulation strategies of micro-casting from titanium (Ti-6Al-4V) swarf - Mozhi Varman, J. P. Arul; Wainwright, James; Suder, Wojciech; Sivarupan, Tharmalingam; Georgarakis, Konstantinos; Salonitis, Konstantinos; Jolly, Mark R.; Williams, Stewart W. (Springer, 2026)
One way of reducing the CO2 footprint for titanium alloys can be by the innovative re-use of machining by-products (swarf). This paper will present modeling and simulation for micro-sized casting in Ti-6Al- 4V (Ti64) swarf, with the ultimate aim of the development of continuous casting applications. Finite Element (FE) modeling is employed to predict thermomechanical behaviour enabling optimisation of heat transfer coefficients for enhanced process control. Computational Fluid Dynamics (CFD) simulation is used to simulate melt flow within a micro-scale crucible to ensure reliable molten metal delivery. Using simulation tools enables rapid design iteration and process tuning without extensive trial-and-error experimentation. This work could contribute to circular economy practices and reinforces the role of digital twins in advancing net zero manufacturing goals in metal manufacturing processes.
Keywords: 4014 Manufacturing Engineering; 40 Engineering; 12 Responsible Consumption and Production; Titanium alloys; continuous casting; Finite Element Analysis; CFD Simulation; net zero